PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLE NON EXAMPLE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III MI AN NASIHAH MANGGALA SEMPURNA KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Marliza Marliza; Lazim. N Lazim. N; Zulkifli Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak :The backround of This research is process learning class lll Ml An Nasiah Manggala Sempurna Kecematan Tanah Putih Kabupaten Rokan Hilir. Study of Ips still domination with the teacher so make the students passive and study achievement is not satisfied with the scor average in on KKM. This research study of porpuse to know or unknow the influence cooperative modelying type example non example decent individual or classical with result learn students class 111the study of IPS MI An Nasiah manggala Sempurna Kecematan Tanah Putih Kabupaten Rokan Hilir.This research doing 22 students. Collegue the data with observation used sheet observation for model of data to learn cooperative type example non example. Through UAS 1 and UAS 11 for data learning. The result of this rise in cycles first than it was before the act or before PTK. The result of the study which occurs before held PTK and cycle increase of 1 15,20% for this cycle 1 the student have finisih with the total 12 students with finish 60%, while in cycle of 2 happened increase with the total 30% with finish of students 15,19, for cycle 11 increase the total 90% so, happened goald difference increase with cycle 1 and cycle 11 with total 30%. While the students activities for first meeting cycle 1 with total 53,5%, second meeting with total 67,75% and cycle 11 for first meeting with total 89,28%, second meeting with total 96,48% so, between cycle 1 and cycle 11 happened increase with total 32,26%. From this research and matery have explanation that with used model cooperative learning type of NHT. It is true then activitias and learning of students happened increase more is very good. This information of cooperative learning type NHT can improve increase study of students IPS class 111 Mi An Nasihah manggala Sempurna Kecamatan Tanah Putih Kabupaten Rokan Hilir. “received”.Keywords. Kooperatif learning model Numbered Head Together and achievement